Complete mitochondrial genome of a Toque Macaque (Macaca sinica). Issue 1 (2nd January 2018) - Roos, Christian
Abstract: The Toque macaque ( Macaca sinica ) is the only macaque species on Sri Lanka and endemic to the island. The newly generated mitochondrial genome (Genbank accession number MG870385), obtained from a captive individual, has a length of 16, 525 bp and exhibits the typical structure of mammalian mitochondrial genomes. Phylogenetically, the Toque macaque is nested within the Macaca sinica species group and represents a sister lineage to a M. assamensis/M. thibetana clade. The new data help to further illuminate and better understand the complex phylogeny of macaques.